2018
DOI: 10.2139/ssrn.3260626
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation, Discounting, and the Effects of Delayed Costs and Benefits

Abstract: Numerous studies have investigated how people resolve intertemporal trade-offs in individual decision making, but little is known about how the timing of costs and benefits affects behavior in strategic decision situations. Here, we experimentally study how delayed costs and/or benefits affect cooperation in a social dilemma situation. We find that cooperation is substantially reduced (increased) when only the benefits (costs) of cooperation are shifted towards the future. We show that the change in contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Beliefs were incentivized using the most likely interval elicitation rule (MLI) method as proposed bySchlag and van der Weele (2015).6 After the second part, there was one additional task in which participants faced a price list to elicit their time preferences. This data was used for another paper (seeKölle and Lauer (2019) for further details).…”
mentioning
confidence: 99%
“…Beliefs were incentivized using the most likely interval elicitation rule (MLI) method as proposed bySchlag and van der Weele (2015).6 After the second part, there was one additional task in which participants faced a price list to elicit their time preferences. This data was used for another paper (seeKölle and Lauer (2019) for further details).…”
mentioning
confidence: 99%
“…Our results highlight the importance of individual time preferences for successful cooperation under risk of collapse. Since behavioral experiments have shown that people do discount (37)(38)(39), this calls for experimental designs to investigate how human time preferences influence the challenge to avoid collapse collectively. It is important to test, for example, whether one can distinguish with human players between a coordination challenge and a comedy and if so, do they experience a black hole; whether the critical collapse impact at the game regime borders indeed scales with N at large N , and whether these critical N /m are independent of the public good enhancement factor f .…”
Section: Discussionmentioning
confidence: 99%
“…benefits and costs (37,38). This holds true when, additionally, catastrophic tipping is considered (39).…”
Section: Significancementioning
confidence: 91%
See 1 more Smart Citation
“…Several studies hypothesized that generosity decreases in a nonconstant hyperbolic fashion across time delays (e.g., Kovarik, 2009;Lu et al, 2023Lu et al, , 2022Ogawa & Ida, 2015). By contrast, some studies do the exact opposite (e.g., Andreoni & Serra-Garcia, 2021;Breman, 2011), yet others find no effect (Kölle & Lauer, 2019). Furthermore, even the theoretical explanations proposed to explain these results seem inconsistent.…”
Section: Introductionmentioning
confidence: 99%